Institutionalizing Waqf Literacy: A Critical Governance Analysis of the Indonesian Waqf Board’s Communication Strategies - Furqon, Ahmad; Anwar, Khoirul; Fuadi, Nasrul Fahmi Zaki; Septiana, Yunita Dewi; Kacem, Fatma (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
Public understanding of waqf in Indonesia remains limited, constraining its socio-economic potential, and is often treated as a mere educational deficit rather than a governance issue. This study examines the role of the Indonesian Waqf Board (BWI) in enhancing waqf literacy by analyzing how literacy initiatives are designed, implemented, evaluated, and institutionally mediated within Indonesia’s waqf governance system. Using a qualitative, document-based descriptive review that integrates a conceptual–normative approach with comparative institutional analysis, the research draws on BWI Annual Reports (2019–2023), the BWI Strategic Plan (2020–2024), and peer-reviewed literature. The findings show that BWI emphasizes productive waqf, multi-channel digital dissemination, and empowerment-oriented narratives, yet evaluates effectiveness primarily through output-based indicators that undercapture comprehension, engagement, and trust formation. Literacy outcomes are further shaped by regulatory overlap, digital asymmetry, resource allocation patterns, and limited participatory mechanisms. The study concludes that waqf literacy is institutionally mediated and governance-driven, underscoring the need for stronger accountability design, evaluative reform, and regulatory coherence.